Foreign Direct Investment in Latin America and the Caribbean 2018 - Nations Unies (United Nations, 2018)
This publication sets out and analyses the main foreign direct investment (FDI) trends in the countries of Latin America and the Caribbean. In 2017, certain trends that had already emerged in the global economic landscape became more established. In particular, announcements of potential restrictions on trade and pressures to relocate production to developed countries were confirmed. At the same time, China has taken steps to restrict outflows of foreign direct investment (FDI) in order to align these flows with its strategic plan. Adding to these factors is the expansion of digital technologies, whose international expansion requires smaller investments in tangible assets. Firms in these areas are heavily concentrated in the United States and China, which reduces the need for cross-border mergers and acquisitions.